Surface Microstructuring of Steel Components for CVD Diamond Coating by Ultrasonic Vibration Superimposed Face Milling using Tailored Tools - Börner, Richard; Göltz, Maximilian; Helmreich, Thomas; Schubert, Andreas; Rosiwal, Stefan (Procedia CIRP, 2020)
Diamond coatings applied by chemical vapor deposition (CVD) provide extraordinary properties concerning hardness and wear resistance, which enables an increase of the performance or lifetime of highly stressed components. In particular, the combination of steel substrates and diamond coatings allows for numerous applications in several sectors of industry. However, there are significant challenges considering the coating adhesion strength. For example, the mismatch concerning the thermal expansion of steel and diamond commonly leads to a delamination of the coating. Thus, a suitable pre-treatment of the substrate surface is compulsory. With the aim of improving CVD diamond coating adhesion, ultrasonic vibration superimposed machining (UVSM) is applied when doing face milling on steel X46Cr13 specimens. The vibration direction is parallel to the tool axis and perpendicular to the feed direction. The tool wear and the surface microstructure are determined by 3D laser scanning microscopy. The investigations show, that predefined microstructuring of the substrate surface by UVSM contributes to an enhancement of the CVD diamond coating adhesion, especially regarding coatings with a thickness up to 10 μm. This can be referred to a better distribution or a reduction of thermally induced residual stresses in the diamond layer. However, a reliable generation of deterministic microstructures by UVSM significantly depends on the wear behavior of the tool. Uncoated cemented carbide grades exhibit considerable deficits reflecting in rapid tool wear. Therefore, adapted tool coatings are experimentally investigated, which result in an increase of the tool life and a reduction of the geometrical deviations of the microstructures. With an appropriate system of surface microstructure and coating, for example for tribological applications substantial improvements in terms of wear resistance and coefficient of friction are expected.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Diamond coating; Microstructure; Ultrasonic vibration superimposed machining